Mediating role of Innovation and Enterprise Size between Entrepreneur and Enterprises Performance - Riyadh Mahmood, Yousif; Dekhn Hamzah, Khitam (Opción, 2019)
The authors tried to identify mediating role of innovation and moderating role of size of enterprise in the relationship between entrepreneurial orientation and performance of Micro and Small Enterprises via survey research methods. As a result, the size of the enterprises moderates the relationship between risk-taking and performance, pro-activeness and performance and innovation and performance. In conclusion, entrepreneurial orientation and innovation are very important for improvement in performance of SMEs. Innovation plays a significant mediating role to enhance performance. The degree of entrepreneurial orientation and the level of innovation is higher in small enterprises as compared to micro enterprises.